Conversational AI: Dialogue Systems, Conversational Agents, and Chatbots by Michael McTear - Seminck, Olga (Computational linguistics - Association for Computational Linguistics, 2023)
Conversational AI: Dialogue Systems, Conversational Agents, and Chatbots by Michael McTear ( Ulster University). Morgan & Claypool (Synthesis Lectures on Human Language Technologies, edited by Graeme Hirst), 2020, 233 pp; paperback, ISBN 9781636390314, $74.99a; hardcover, ISBN 9781636390338; ebook, ISBN 9781636390321, $59.99; doi:10.2200/S01060ED1V01Y202010HLT048.